A Novel Periplasmic Protein, VrpA, Contributes to Efficient Protein Secretion by the Type III Secretion System in Xanthomonas spp. - Xiaofeng Zhou; Xiufang Hu; Jinyun Li; Nian Wang (Molecular Plant-Microbe Interactions, 2015)
Efficient secretion of type III effector proteins from the bacterial cytoplasm to host cell cytosol via a type III secretion system (T3SS) is crucial for virulence of plant-pathogenic bacterium. Our previous study revealed a conserved hypothetical protein, virulence-related periplasm protein A (VrpA), which was identified as a critical virulence factor for Xanthomonas citri subsp. citri. In this study, we demonstrate that mutation of vrpA compromises X. citri subsp. citri virulence and hypersensitive response induction. This deficiency is also observed in the X. campestris pv. campestris strain, suggesting a functional conservation of VrpA in Xanthomonas spp. Our study indicates that VrpA is required for efficient protein secretion via T3SS, which is supported by multiple lines of evidence. A CyaA reporter assay shows that VrpA is involved in type III effector secretion; quantitative reverse-transcription polymerase chain reaction analysis suggests that the vrpA mutant fails to activate citrus-canker-susceptible gene CsLOB1, which is transcriptionally activated by transcription activator-like effector PthA4; in vitro secretion study reveals that VrpA plays an important role in secretion of T3SS pilus, translocon, and effector proteins. Our data also indicate that VrpA in X. citri subsp. citri localizes to bacterial periplasmic space and the periplasmic localization is required for full function of VrpA and X. citri subsp. citri virulence. Protein–protein interaction studies show that VrpA physically interacts with periplasmic T3SS components HrcJ and HrcC. However, the mutation of VrpA does not affect T3SS gene expression. Additionally, VrpA is involved in X. citri subsp. citri tolerance of oxidative stress. Our data contribute to the mechanical understanding of an important periplasmic protein VrpA in Xanthomonas spp.